Targeting MYCN in Pediatric and Adult Cancers - Liu, Zhihui; Chen, Samuel S.; Clarke, Saki; Veschi, Veronica; Thiele, Carol J. (Frontiers in Oncology, 2021)
The deregulation of MYC family oncogenes including c-MYC, MYCN and MYCL occurs in many types of cancers and frequently marks those associated with a poor prognosis. The majority of functional studies have focused on c-MYC due to its broad expression profile in human cancers. The existence of highly conserved functional domains between MYCN and c-MYC suggest similar activities. MYC encodes a basic helix-loop-helix-leucine zipper (bHLH-LZ) transcription factor (TF) whose central oncogenic role in many human cancers makes it a highly desirable therapeutic target. Historically, as a TF, MYC has been regarded as “undruggable”. Thus, recent efforts focus on investigating methods to indirectly target MYC to achieve anti-tumor effects. This review will mainly summarize the recent progress in understanding the function of MYCN. It will explore efforts at targeting MYCN, including strategies aimed at suppression of MYCN transcription, destabilization of MYCN protein, inhibition of MYCN transcriptional activity, repression of MYCN targets and the utilization of MYCN overexpression dependent synthetic lethality.